The global burden of disease study 2010: Interpretation and implications for the neglected tropical diseases - Hotez, Peter J.; Alvarado, M.; Basanez, M.-G.; Bolliger, I.; Bourne, R.; Boussinesq, M.; Brooker, S.J.; Brown, A.S.; Buckle, G.; Budke, C.M.; Carabin, H.; Coffeng, L.E.; et al. (Public Library of Science, 2014)
The publication of the Global Burden of Disease Study 2010 (GBD 2010) and the accompanying collection of Lancet articles in December 2012 provided the most comprehensive attempt to quantify the burden of almost 300 diseases, injuries, and risk factors, including neglected tropical diseases (NTDs) [1]–[3]. The disability-adjusted life year (DALY), the metric used in the GBD 2010, is a tool which may be used to assess and compare the relative impact of a number of diseases locally and globally [4]–[6]. Table 1 lists the major NTDs as defined by the World Health Organization (WHO) [7] and their estimated DALYs [1]. With a few exceptions, most of the NTDs currently listed by the WHO [7] or those on the expanded list from PLOS Neglected Tropical Diseases [8] are disablers rather than killers, so the DALY estimates represent one of the few metrics available that could fully embrace the chronic effects of these infections.